Exploring students' experiences of a blended learning pre-registration midwifery education programme. - Nash, Helena; Hayward, Melanie (British Journal of Midwifery, 2025)
Background/Aims: Blended learning is increasingly adopted in pre-registration midwifery education because of its pedagogical benefits, yet little research explores student midwives' lived experiences of such programmes. This study examined the experiences of final-year student midwives undertaking a 3-year blended learning programme, to enhance educator understanding. Methods: This qualitative interpretative phenomenological study involved four purposively selected students from a university in southeast England. Semi-structured interviews were conducted, transcribed verbatim and analysed using interpretative phenomenological analysis. Results: Four experiential themes were found: the safety and welfare of learning, ownership and autonomy, the gravitational pull of friendships, and the nurturing aspect of peer relationships. Students reported increased self-efficacy, academic and professional growth, and the significance of connection and belonging. Conclusions: Conclusions Blended learning supports recruitment, retention and student wellbeing, encouraging a compassionate learning environment that enhances preparedness for midwifery practice. Implications for practice: It is suggested that blended learning supports the development of compassionate and more autonomous individuals who are equipped to work as professional midwives in a digitally evolving clinical environment.